Social Relationship Dynamics in a Remote Work Environment: the Psychological Impact of Long-Term Telecommuting - Lolowang, Roosye Marie (World Psychology, 2024)
Remote working or telecommuting has become an increasing trend, mainly driven by technological advancements and the global pandemic situation. The dynamics of social relationships in the work environment have greatly changed as a result of the transition from physical offices to virtual offices. Both workers and organizations must adjust to the dynamics of social relationships in a remote work environment, as telecommuting offers flexibility and autonomy. This study was conducted with the aim of understanding how remote work affects employees' mental health such as stress levels, anxiety, depression, and job satisfaction levels. As well as evaluating the changes that occur in the social interactions that take place among workers and how it impacts team dynamics, collaboration, and company culture. The method used by researchers in researching Social Relationship Dynamics in Remote Work Environments: The Psychological Impact of Long-Term Telecommuting is to use a quantitative method. The data obtained by researchers was obtained from the results of distributing questionnaires. The results of data acquisition will also be tested again using the SPSS application. From the research results, it can be seen that the Dynamics of Social Relations in a Remote Work Environment: The Psychological Impact of Long-Term Telecommuting, has positive and negative effects. On the other hand, it is mentioned as the main benefit of being independent and reducing the burden of travel, and on the other hand, the loss of face-to-face interactions and miscommunication through digital media are the main problems. From this study, we can conclude that the long-term use of telecommuting has a complex impact on social relationship dynamics and psychological well-being of employees. While independence and flexibility are key advantages, challenges in communication and social interaction also require special attention.